260 T cell infiltrating repertoire diversity is associated with enhanced survival following neoadjuvant therapy in patients with resectable pancreatic cancer. (9th November 2020) - Murthy, Pranav; Saini, Pragosh; Russell, Kira; Pan, Wenjing; Weber, Daniel; Byrne-Steele, Miranda; Han, Jian; Espina, Viginia; Liotta, Lance; Zeh, Herbert; Bahary, Nathan; Singhi, Aatur; et al.
Abstract : Background: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy, characterized by a desmoplastic stromal reaction and an immunosuppressive tumor microenvironment (TME) 1 . The metabolic stress within the PDAC TME promotes autophagy, a form of programmed cell survival associated with chemotherapeutic resistance and immune evasion. 2, 3 Methods: We conducted a randomized phase II study of preoperative gemcitabine and nab-paclitaxel with or without autophagy inhibition with oral hydroxychloroquine (HCQ) in patients with resectable PDAC. Autophagy inhibition increased Evans Grade histopathologic response and immune infiltrate. 4 Utilizing multiplex immunohistochemistry and dimer avoidance multiplex PCR-NGS 5 in a subset of RNA extracted FFPE tumor specimens, we evaluated the adaptive immune response and immune correlates of response. Results: Patients receiving HCQ had a greater CD4/CD8 immune infiltration (p = 0.033). Independent of treatment, a higher tumor immune infiltration score, 6 was associated with improved overall survival (p = 0.035). Bulk tumor immunosequencing revealed a clonally expanded T cell receptor (TCR) Vβ (115±84 unique CDR3s (uCDR3s) of 3.3 × 10 4 ±2.4 total CDR3s) and B cell receptor (BCR) IgH (9.8 × 10 4 ±5.2 uCDR3s of 1.4 × 10 5 ±0.76 total CDR3s) repertoire compared to a paucity of TCR Vδ clones (2±1 uCDR3s of 43±60 total CDR3s). Patients with a higher than median TCR Vβ Diversity 50 Index (D50, proportion of uCDR3s that make up 50% of the total CDR3s) had significantly higher tumor CD4 (p = 0.003) and CD8 (p = 0.031) counts. Patients with a higher than median TRC Vβ D50 also had a reduced lymph node ratio (p = 0.039) and greater overall survival (p = 0.037, figure 1 ). Conversely, patients with a higher than median BCR IgH D50 had worse overall survival (p = 0.0241). Given the dichotomy of the TCR and BCR repertoire diversity and association with clinical outcome, we further analyzed the individual ratio of TRC Vβ:BCR IgH CDR3s and found that patients with a higher than median TRC Vβ:BCR IgH ratio had a greater Evan's Grade histopathologic response (p = 0.069). Conclusions: PDAC TIL repertoire with high TCR Vβ diversity is associated with decreased positive lymph node ratio and greater overall survival following neoadjuvant therapy. The divergent outcomes associated with increased intratumoral TCR and BCR diversity suggest a host response that may favor opposing T and B cell lymphocytic expansion. Regulation of this relationship may be explained by tumor MHC class I expression[3] or the presence of CD141+ cross presenting dendritic cells 7, 8 and tertiary lymphoid structures, 9 currently under investigation. Examination of repertoire modulating therapies is warranted. Trial Registration: This trial (NCT01978184 ) was approved by the protocol review committee and IRB 13–074 at the University of Pittsburgh and performed in full accordance with the guidelines for good clinical practice and the Declaration of Helsinki. Written informed consent was obtained from all patients prior to any protocol treatment. References: Ho WJ, Jaffee EM, Zheng L. The tumour microenvironment in pancreatic cancer - clinical challenges and opportunities. Nat Rev Clin Oncol 2020;17(9):527–540. Boone BA, Zeh HJ, 3rd, Bahary N. Autophagy inhibition in pancreatic adenocarcinoma. Clin Colorectal Cancer 2018;17(1):25–31. Yamamoto K, Venida A, Yano J, et al. Autophagy promotes immune evasion of pancreatic cancer by degrading MHC-I. Nature 2020;581(7806):100–105. Zeh HJ, Bahary N, Boone BA, et al. A Randomized phase ii preoperative study of autophagy inhibition with high-dose hydroxychloroquine and gemcitabine/nab-paclitaxel in pancreatic cancer patients. Clin Cancer Res 2020;26(13):3126–3134. Han J, Lotze MT. The adaptome as biomarker for assessing cancer immunity and immunotherapy. Methods Mol Biol 2020; 2055 :369–397. Hwang WT, Adams SF, Tahirovic E, Hagemann IS, Coukos G. Prognostic significance of tumor-infiltrating T cells in ovarian cancer: a meta-analysis. Gynecol Oncol . 2012;124(2):192–198. Spranger S, Dai D, Horton B, Gajewski TF. Tumor-Residing Batf3 Dendritic Cells Are Required for Effector T Cell Trafficking and Adoptive T Cell Therapy. Cancer Cell 2017;31(5):711–723 e714. Jang JE, Hajdu CH, Liot C, Miller G, Dustin ML, Bar-Sagi D. Crosstalk between regulatory T cells and tumor-associated dendritic cells negates anti-tumor immunity in pancreatic cancer. Cell Rep 2017;20(3):558–571. Bruno TC. New predictors for immunotherapy responses sharpen our view of the tumour microenvironment. Nature 2020;577(7791):474–476.